Parallel Architecture Approach to Spanish Verbal Derivation with the Causative Prefix en–. - GarcÍa, Ernesto Wong (Forum for Modern Language Studies, 2019)
This paper presents an analysis of a corpus of Spanish causative verbs formed with the prefix en–, framed in terms of the Parallel Architecture (PA) theory. By segmenting the units, we identify five specific morphological schemas, all instances of a single general schema. By analysing dictionary definitions, we identify one general meaning schema, realized in nine specific schemas, which are modelled using the tools of Conceptual Semantics. By analysing how these verbs behave in sentences, we identify one general syntactic schema, realized in three specific schemas. We also look at the sound structure of these verbs, and explore the links between the three kinds of structure (sound, syntax and meaning), the production of redundancies (or lack thereof) when the verbs take complements, and we formulate the problems of predicting the meaning of the verb from the meaning of the base, and of accounting for figurative meanings.